Gender Equality in Education: Analysis of Global Education Policy and Its Implementation in Indonesia - Solihin, Ihin; Erihadiana, M. (Universitas Pahlawan Tuanku Tambusai, 2026)
This research aims to analyze the influence of global policies on gender equality on the formulation and implementation of education policies in Indonesia. Using a thematic narrative review approach, this study synthesizes academic literature, global policy documents, and national implementation reports to trace the relationship between international frameworks such as SDG 4.5 and UNESCO guidelines with gender-responsive policies at the national level and practices in schools. The analysis results show that although global policies have influenced the direction of national regulations, implementation at the school level is still uneven and does not fully reflect the principle of structural equality. Gaps exist in cultural aspects, teacher capacity, monitoring mechanisms, and the policy adaptation process. This research makes a theoretical contribution to the development of policy transfer studies in gender education and offers a conceptual model that can be used for further research and more effective policy formulation.